2022
DOI: 10.3390/ijms23094610
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Biomarkers and Their Implications for the Early Diagnosis of Selected Neurodegenerative Diseases

Abstract: The degeneration and dysfunction of neurons are key features of neurodegenerative diseases (NDs). Currently, one of the main challenges facing researchers and clinicians is the ability to obtain reliable diagnostic tools that will allow for the diagnosis of NDs as early as possible and the detection of neuronal dysfunction, preferably in the presymptomatic stage. Additionally, better tools for assessing disease progression in this group of disorders are also being sought. The ideal biomarker must have high sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 161 publications
0
19
0
Order By: Relevance
“…In recent years, most research on the role of ncRNAs from different sources in AD have been published. In fact, ncRNAs are not only found in nerve cells but can also be detected in blood and cerebrospinal fluid, suggesting that ncRNAs from different tissue may have different clinical significance ( Nikolac Perkovic et al, 2021 ; Doroszkiewicz et al, 2022 ). In fact, the expression level of ncRNAs in different tissues may also be different, which also makes it difficult to explore biomarkers for AD.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, most research on the role of ncRNAs from different sources in AD have been published. In fact, ncRNAs are not only found in nerve cells but can also be detected in blood and cerebrospinal fluid, suggesting that ncRNAs from different tissue may have different clinical significance ( Nikolac Perkovic et al, 2021 ; Doroszkiewicz et al, 2022 ). In fact, the expression level of ncRNAs in different tissues may also be different, which also makes it difficult to explore biomarkers for AD.…”
Section: Discussionmentioning
confidence: 99%
“…A group of miRNAs have been reported as prognostic biomarkers for ALS [ 201 ]. After an investigation of 252 ALS patients, it was concluded that circulating miR-181 was a prognostic biomarker for the disease [ 202 ].…”
Section: Mirna-based Bioanalysis In the Diagnosis Of Neurodegenerativ...mentioning
confidence: 99%
“…Moreover, in patients with ALS, some studies have shown the changing patterns of methylation in ALS-related genes [ 57 , 58 , 59 ] and connected the engagement of the epigenetic mechanisms in motor neuron apoptotic cell death through DNA methylation, which is essential during the development of the nervous system and could be relevant to human ALS pathobiology [ 60 ]. The results of several studies suggest that epigenetic changes (through methylation and noncoding RNAs) may represent new biomarkers and contribute to the development of new ALS therapies (reviewed in [ 61 , 62 , 63 ]). Moreover, we propose that the overlap and correlation in the expression of the selected biomarkers during early CNS development and in ALS patients could narrow down the number of potential candidates, as well as open new insights into disease pathogenesis.…”
Section: Genetics Of Alsmentioning
confidence: 99%